Identification and analysis of stem‐specific promoters from sugarcane and energy cane for oil accumulation in their stems. Issue 9 (27th June 2021) - Wang, Jiang; Li, Yaxin; Wai, Ching Man; Beuchat, Gabriel; Chen, Li‐Qing
Abstract: Considerable recent progress has been achieved in bioengineering oil accumulation in the vegetative tissues of plants, opening an opportunity for large scale production of biodiesel, jet fuel, lubricants, and high‐value lipid bioproducts. For the highly productive C4 crops, such as sugarcane, energy cane, Miscanthus, and fiber sorghums, the bulk of the biomass is the stem. However, little success has been made in accumulating oil in the stem. Since engineering a trait with a constitutive promoter often results in pleiotropic effects that counter trait improvement, identification of stem parenchyma‐specific promoters is a prerequisite for efficient use of the ample photoassimilates stored in mature stem parenchyma cells. In this study, we first identified two TST genes encoding homologues of tonoplast sugar transporters that were strongly and almost exclusively expressed in the stems of canes via a combination of RNA‐seq atlas analysis, in silico analysis of a sugarcane genome, phylogenetic analysis, and quantitative PCR analysis. They were further confirmed in the pith parenchyma cells of the mature stem by RNA in situ hybridization. When fused with the β‐Glucuronidase (GUS) reporter gene, the promoters of two alleles, TST2b‐1A and TST2b‐1C, from one TST gene demonstrated that they could drive the GUS expression exclusively in the stem in Arabidopsis. Abstract : Constitutively engineering oil biosynthesis throughout the bioenergy plant may produce pleiotropic effects, such as growth arrest. Therefore, manipulations should be restricted to a specific tissue or cell type, such as mature stem parenchyma cells, where tremendously stored photoassimilates are available for efficient oil conversion. Two stem‐specific promoters were identified from canes in this study.